1983
DOI: 10.1038/303621a0
|View full text |Cite
|
Sign up to set email alerts
|

Transmitter-like action of ATP on patched membranes of cultured myoblasts and myotubes

Abstract: The concept of purinergic neurotransmission, first proposed by Burnstock, has been confirmed in various cell types. We show here, by the patch-clamp method, that external ATP in micromolar concentrations (1-100 microM) activates cation channels in the membranes of fusion-competent myoblasts and myotubes. In cell-attached membrane patches of myoblasts and myotubes the mean number of simultaneously activated channels increases with time after external ATP application. In myoblasts only one population of channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(70 citation statements)
references
References 8 publications
3
67
0
Order By: Relevance
“…Localization of zP2X 5.1 The existence of an ion channel sensitive to ATP in skeletal muscle was first suggested many years ago [24]. Although subsequent studies confirmed the existence of ATP-sensitive ion channels in avian skeletal muscle, they suggested that the single-channel currents had a very low unitary conductance compared to the initial report [25,26].…”
Section: Cloning Of Zebrafish P2x Receptor Cdnas Uncovered Three New mentioning
confidence: 59%
See 1 more Smart Citation
“…Localization of zP2X 5.1 The existence of an ion channel sensitive to ATP in skeletal muscle was first suggested many years ago [24]. Although subsequent studies confirmed the existence of ATP-sensitive ion channels in avian skeletal muscle, they suggested that the single-channel currents had a very low unitary conductance compared to the initial report [25,26].…”
Section: Cloning Of Zebrafish P2x Receptor Cdnas Uncovered Three New mentioning
confidence: 59%
“…Evidence from other species had suggested that ATP responses would be found in zebrafish muscle. For instance, contractions of frog skeletal muscle in response to extracellular ATP were first reported in the 1940s [39], and the electrophysiological characterization of P2X receptor properties on cultured chick myoblasts and myotubes was explored in detail in the 1980s [24,25,40]. In the 1990s, cloning studies demonstrated that P2X 5 was expressed in chick skeletal muscle, and when chick P2X 5 was expressed in oocytes, the currents exhibited properties expected for the endogenous chick receptors [41].…”
Section: Discussionmentioning
confidence: 99%
“…The original evidence that ATP directly gates the opening of ion channels was based on whole-cell and single-channel recordings from embryonic chick skeletal muscle myotubes (Kolb and Wakelam, 1983). Subsequent studies in chick and frog showed striking developmental regulation of these channels; they disappear during late embryogenesis but reappear in the adult after denervation (Hume and Honig, 1986;Igusa, 1988;Thomas and Hume, 1990a;Thomas et al, 1991;Wells et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics, as well as the nucleotide specificity (ATP > ATP-gamma-s > ADP) are very similar to the results reported here, in which the TEA-sensitive effiux appears to be due to the activation of a Ca~+-sensitive BK channel, and the TEA-insensitive channel may include the activation of the nonspecific cation channel. Extracellular ATP also activated a nonselective cation conductance in a mouse macrophage cell line (Buisman et al, 1988), rat vas deferens (Freil, 1988), and cultured chick myoblasts (Kolb and Wakelam, 1983), and a Ca2+-sensitive K + channel in cultured bovine aortic endothelial cells (Sauve et al, 1988).…”
Section: Atp and Carbachol Activate K + Efflux Through Multiple Pathwaysmentioning
confidence: 99%